Alternate-day fasting induces metabolic and morphofunctional changes in the gastrointestinal tract of male rats - Simoes Beckmann, Ana Paula; Gama, Loyane Almeida; Rocha Machado, Mariana Pirani [UNESP]; Luz Alves, Wellington David; Cora, Luciana Aparecida; Americo, Madileine Francely (Canadian Science Publishing, 2023)
Alternate-day fasting (ADF) is a nutritional intervention with modulatory and overall protective effects, but its role in the gastrointestinal (GI) tract is still uncertain. The aim of this study was to investigate the influence of ADF on the metabolic patterns and morphofunctional motility of the GI tract in rats. Thirty-two male Wistar rats were allocated into groups: control for 15 days (CON 15, n = 8), control for 30 days (CON 30, n = 8), ADF for 15 days (ADF 15, n = 8), and ADF for 30 days (ADF 30, n = 8). Blood glucose, body weight, and food and water consumption were measured. Frequency and amplitude of gastric contractions as well as gastric emptying time, small intestinal transit time, and cecum arrival time were measured. Intestinal histomorphometric, relative weight of organs, lipidogram, and leptin levels were also evaluated. ADF decreased water consumption and food consumption. The weight gain decreased; however, the relative kidney weight increased. ADF triggered an increase in the amplitude of gastric contractions and accelerated gastric emptying. However, small intestinal transit time was delayed in both ADF groups. Total cholesterol, triglycerides, non-HDL cholesterol, and very low-density lipoprotein cholesterol levels decreased, whereas villus height, depth of the crypts and thickness of the circular, and longitudinal muscular layers of intestine increased after ADF. In conclusion, our results showed ADF exert an effect on both metabolism and GI motility and impacts on overall digestive functions.
Keywords: gastrointestinal transit; intermittent fasting; intestinal morphology; metabolic response; alternating current bio-susceptometry